Fuzzy arithmetical modeling and simulation of vibrating structures with uncertain parameters - Hanss, M.; Willner, Kai (Noise and Vibration Engineering, 2004)
A general method for the simulation and analysis of systems with uncertain parameters is presented. In this concept, the uncertain parameters are modeled by fuzzy numbers in contrast to random numbers in stochastic approaches. After an introduction to fuzzy arithmetic, the transformation method is presented a practical implementation which allows the use of the fuzzy concept in conjunction with existing simulation environments. As a result of the simulation of the model, it is possible to quantify the overall uncertainty of the outputs, providing a worst-case scenario. Additionally, the uncertain model parameters can be rated with respect to their influence on the overall output uncertainty. As examples, some finite element applications of the fuzzy arithmetical approach are presented and discussed: the frequency response function of a vibrating plate and the vibration behavior of an engine hood in the presence of uncertain model parameters.
UnivIS-Import:2015-04-16:Pub.2004.tech.FT.FT-TM.fuzzya_4